2018
DOI: 10.1016/j.snb.2018.07.101
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria electrical detection using 3D silicon nanowires based resistor

Abstract: This device offers promising potentialities taking advantages of integration into CMOS 2 platform for alternative direct electrical detection of bacteria to monitor the contamination in environment for hygiene applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…5a served as reference to control the binding of bacteria with antibodies. The curve is quasi-symmetrical with a non-ohmic behaviour at low voltages, as previously observed in a preliminary study with similar resistors for E. coli detection for yes/no diagnosis, for which no functionalization of silicon nanowires was performed (Le Borgne et al, 2018). This behaviour is related to the electrical model of the global electrical resistance (Rtot) of the resistor (Fig.…”
Section: Electrical Measurements Before E Coli Immobilizationsupporting
confidence: 75%
See 2 more Smart Citations
“…5a served as reference to control the binding of bacteria with antibodies. The curve is quasi-symmetrical with a non-ohmic behaviour at low voltages, as previously observed in a preliminary study with similar resistors for E. coli detection for yes/no diagnosis, for which no functionalization of silicon nanowires was performed (Le Borgne et al, 2018). This behaviour is related to the electrical model of the global electrical resistance (Rtot) of the resistor (Fig.…”
Section: Electrical Measurements Before E Coli Immobilizationsupporting
confidence: 75%
“…Interconnected nanowires ensure electrical contact between the two doped polycrystalline silicon electrodes SiNWs (Pichon et al, 2015). In order to optimise the detection of bacteria, the electrodes were made with a higher number of teeth per unit area than the previous reported structures ( Le Borgne et al, 2018), as shown on Scanning Electron Microscopy (SEM) images (Fig. 1d).…”
Section: Fabrication Of Interdigitated Sinws Electrode Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, gold does not oxidize, increasing its catalytic activity. Gold-catalyzed SiNWs are well controlled and already integrated into prototypes such as transistors [23], biosensors [24], and photo-anodes [25].…”
Section: Indium As Catalyst For Silicon Nanowires' Growthmentioning
confidence: 99%
“…Cordoba et al [18] fabricated tunnel junction using doped n-type and p-type SiNW grown by VLS mechanism. Some group [19] found that bacteria could be detected through the drastic reduction of resistance of doped SiNW in contact with bacteria. Ahmed et al [20] fabricated high performance radial junction solar cell using doped SiNW grown via VLS mechanism using plasma-enhanced chemical vapor deposition (PECVD).…”
Section: Introductionmentioning
confidence: 99%